Macroeconomic variables and long-term stock market performance: A panel ARDL cointegration approach for G7 countries - Andreas Humpe; David G. McMillan (Cogent Economics & Finance, 2020)
Based on the present value model for stock prices, we utilise a pooled mean group estimator for panel ARDL cointegration to estimate the long-run relationship between G7 stock prices and macroeconomic variables over the last 40 years. We find a positive long-run relation between stock prices, industrial production and consumer prices as well as a negative relationship with real 10-year interest rates.
Keywords: C32; E44; G12; G7; 330; cointegration; macroeconomy; stock market